Hamstring muscle volume as an indicator of sprint performance - Nuell, S.; Illera-Domínguez, V.; Carmona, G.; Macadam, P.; Lloret, M.; Padullés, J. M.; Alomar, X.; Cadefau, J. A. (The Journal of Strength and Conditioning Research, 2021)
This study aimed to compare mechanical properties and performance during sprinting, as well as thigh muscle volumes (MVs), between national-level sprinters and physically active males. In addition, the relationships between thigh MVs and sprint mechanical properties and performance were investigated. Seven male sprinters and 9 actives performed maximal-effort 40-m sprints. Instantaneous velocity was measured by radar to obtain theoretical maximum force (F0), the theoretical maximum velocity (V0), and the maximum power (Pmax). For MV assessment, series of cross-sectional images of each subject's thigh were obtained by magnetic resonance imaging for each of the quadriceps and hamstring muscles and the adductor muscle group. Sprinters were faster over 10 m (7%, effect size [ES] = 2.12, p < 0.01) and 40 m (11%, ES = 3.68, p < 0.01), with significantly higher V0 (20%, ES = 4.53, p < 0.01) and Pmax (28%, ES = 3.04, p < 0.01). Sprinters had larger quadriceps (14%, ES = 1.12, p < 0.05), adductors (23%, ES = 1.33, p < 0.05), and hamstrings (32%, ES = 2.11, p < 0.01) MVs than actives. Hamstrings MV correlated strongly with 40-m sprint time (r = -0.670, p < 0.01) and V0 (r = 0.757, p < 0.01), and moderately with Pmax (r = 0.559, p < 0.05). Sprinters were significantly faster and had greater V0 and Pmax than active males. Larger MVs were found in sprinters' thighs, especially in the hamstring musculature, and strong correlations were found between hamstring MV and sprint mechanical properties and sprint performance.